Machado de Assis e a Língua Portuguesa na segunda metade do século XIX - Martino, Agnaldo Sérgio de (2013)
This essay intends to analyze Machado de Assis chronicles, published in several newspapers of Rio de Janeiro, to highlight the writer/chronicler acting as an observator of the uses at his age, the XIX century, of Portuguese Language, both in ordinary people daily life, and in literary texts, at schools and academies. The quotations made by Machado de Assis in his writings about the language used in Brazil is equivalent to studies about Linguistics usages. Under this assumption, his chronicles published (between 1859 and 1897) stands out the fashionable linguistic sight in the second half of that century. Due to the constant presence of the role of a chronicler, with his discursive strategies, in Rio de Janeiro press, this research aims to prove that our author, besides being an outstanding novelist and short story writer, left also his mark on chronicles gender considered as minor by some literary critics. This striking situation must be recognized and praised in the studies that deal with matters related to Portuguese Language of Brazil in the XIX century right at the time we saw the consolidation of Brazilian nationality feeling and emerged discussions about a possible Brazilian Language